Evaluation of a community-based mentoring program on psychosocial functioning of adolescents with a visual impairment: A randomized controlled trial. (September 2021) - Heppe, Eline CM; Willemen, Agnes M; Kef, Sabina; Schuengel, Carlo
This study evaluated the efficacy of a mentoring program on improving psychosocial functioning of young people with a visual impairment (VI). Furthermore, the impact of experimentally matching mentees to mentors with or without VI on youth outcomes was examined. A total of 76 adolescents with VI (15–22 year; 46% boys) were randomized into a yearlong mentoring program ( n  = 51) or care-as-usual ( n  = 25). Mentoring involved one-on-one activities within community settings. Psychosocial functioning was improved in all participants during the study ( d  = 0.35–1.06); however, mentoring outperformed care-as-usual only for autonomy (95% CI: 0.003, 0.31; d  = 0.44) and competence satisfaction (95% CI: 0.02, 0.34; d  = 0.55), and not for the other six psychosocial outcomes ( d  < 0.36). Matching similarity was not significantly related to the outcomes assessed. Mentoring was of limited benefit for psychosocial functioning of youth with VI. This trial is registered in the Netherlands Trial Register NTR4768.